Micropowder Ca2YMgScSi3O12:Ce Silicate Garnet as an Efficient Light Converter for White LEDs - Shakhno, Anna; Markovskyi, Anton; Zorenko, Tetiana; Witkiewicz-Lukaszek, Sandra; Vlasyuk, Yevheniya; Osvet, Andres; Elia, Jack; Brabec, Christoph; Batentschuk, Miroslaw; Zorenko, Yuriy (Materials, 2022)
This work is dedicated to the crystallization and luminescent properties of a prospective Ca2YMgScSi3O12:Ce (CYMSSG:Ce) micropowder (MP) phosphor converter (pc) for a white light-emitting LED (WLED). The set of MP samples was obtained by conventional solid-phase synthesis using different amounts of B2O3 flux in the 1-5 mole percentage range. The luminescent properties of the CYMSSG:Ce MPs were investigated at different Ce3+ concentrations in the 1-5 atomic percentage range. The formation of several Ce3+ multicenters in the CYMSSG:Ce MPs was detected in the emission and excitation spectra as well as the decay kinetics of the Ce3+ luminescence. The creation of the Ce3+ multicenters in CYMSSG:Ce garnet results from: (i) the substitution by the Ce3+ ions of the heterovalent Ca2+ and Y3+ cations in the dodecahedral position of the garnet host; (ii) the inhomogeneous local environment of the Ce3+ ions when the octahedral positions of the garnet are replaced by heterovalent Mg2+ and Sc3+ cations and the tetrahedral positions are replaced by Si4+ cations. The presence of Ce3+ multicenters significantly enhances the Ce3+ emission band in the red range in comparison with conventional YAG:Ce phosphor. Prototypes of the WLEDs were also created in this work by using CYMSSG:Ce MP films as phosphor converters. Furthermore, the dependence of the photoconversion properties on the layer thickness of the CYMSSG:Ce MP was studied as well. The changes in the MP layer thickness enable the tuning of the white light thons from cold white/daylight to neutral white. The obtained results are encouraging and can be useful for the development of a novel generation of pcs for WLEDs.
CRIS-Team WoS Importer:2022-06-24
Keywords: WLED; phosphor converters; Ca2+-Mg2+-Si4+-based garnets; micropowder; luminescence; Ce3+ multicenters